The primary structure of the human epsilon-globin gene. - Baralle, F; Shoulders, C; Proudfoot, N (1980)
We describe the complete nucleotide sequence of the human epsilon-globin gene including 387 nucleotides of 5' flanking sequence and 301 nucleotides of 3' flanking sequence. The arrangement of coding, noncoding and intervening sequences in this gene is entirely consistent with its identification as the embryonic beta-like globin gene.